(untitled) (Pain medicine, 2022)
The topic of obstetric and gynecological aggression is a widespread topics, but at the same taboo. The reason is the stigma and fear of women who have been subjected to medical violence. This is something that is not spoken out loud, is not put on public display, because behind it lies pain and shame. Therefore, they do not attach any importance to the topic of obstetric violence. According to modern data, every third woman in the world suffers from the inhumane actions of obstetricians. And these actions lead to irreparable consequences in the life of every woman. The purpose of the study is to assess the impact of obstetric violence on the quality of a woman’s life. Background. To identify the main ways of overcoming this problem. It was established that the negative experience of visiting a gynecologist associated with feeling of pain causes a feeling of fear before the next examination, this reduces visits to preventive examinations, which can lead to the detection of diseases at later stages of its development and complicate the treatment. The negative experience of visiting a gynecologist associated with the feeling of pain worsens the quality of life of a woman according to the indicators of the “Mental health” component. Establishing the presence of factors of obstetric and gynecological violence requires psychological assistance to patients and the development of ethical approaches to the provision of medical care by doctors and medical personnel and the improvement of pain relief methods